Improvement of Outcome for Treatment of ‘Restenosis-prone’ Vascular Lesions? Potential Impact of the Paclitaxel dose on Late Lumen Loss in Porcine Peripheral Arteries - Gemeinhardt, Ole; Haase, Tobias; Schnorr, Beatrix; Xie, Jing; Löchel, Melanie; Schütt, Denise; Mittag, Antje; Haider, Wolfram; Bettink, Stephanie; Speck, Ulrich; Tepe, Gunnar (Cardiovascular and interventional radiology, 2022)
Purpose Clinical data indicate that the drug density on drug-coated balloons (DCBs) might have a role on treatment effect and durability. The aim of the current study was to investigate inhibition of neointimal formation and potential adverse effects after treatment with a novel double-dose DCB in swine. Material and methods A four-week study was performed in peripheral arteries of 12 domestic pigs after vessel injury and stent implantation. The novel double-dose DCB with 6-µg paclitaxel (Ptx)/mm 2 balloon surface (1 × 6) was compared to a standard DCB with 3.5 µg Ptx/mm 2 (3.5) and uncoated balloons (POBA). Potential adverse effects were stimulated by using three fully overlapping DCBs with 6 µg Ptx/mm 2 each (3 × 6). Quantitative angiography, histomorphometry and histopathological analyses were performed. Results Higher paclitaxel doses per square millimeter of treated arteries were associated with reduced late lumen loss (LLL) in quantitative angiography 4 weeks after treatment (POBA: 0.91 ± 0.75 mm; 3.5: 0.45 ± 0.53 mm; 1 × 6: 0.21 ± 0.41 mm; 3 × 6: − 0.38 ± 0.65 mm). In histomorphometry, maximal neointimal thickness and neointimal area were the lowest for the 1 × 6 group (0.15 ± 0.06 mm/1.5 ± 0.4 mm 2 ), followed by 3 × 6 (0.20 ± 0.07 mm/1.8 ± 0.4 mm 2 ), 3.5 (0.22 ± 0.12 mm/2.2 ± 1.1 mm 2 ) and POBA (0.30 ± 0.07 mm/3.2 ± 0.7 mm 2 ). Downstream tissue showed histopathological changes in all groups including POBA, in larger number and different quality (e.g., edema, inflammation, vessel wall necrosis, vasculitis and perivasculitis) in the 3 × 6 group, which did not cause clinical or functional abnormalities throughout the study. Conclusion Treatment with the double-dose DCB (6 µg Ptx/mm 2 ) tended to increase inhibition of in-stent neointimal formation and to diminish LLL after peripheral intervention in the porcine model compared to a market-approved DCB with 3.5 µg Ptx/mm 2 .